Extended-pour and conventional alginates: effect of storage time on dimensional accuracy and maintenance of details - Sandro Basso BITENCOURT; Isabela Araguê CATANOZE; Emily Vivianne Freitas da SILVA; Karina Helga Leal TURCIO; Daniela Micheline dos SANTOS; Daniela Atili BRANDINI; Marcelo Coelho GOIATO; Aimée Maria GUIOTTI (Dental Press Editora, 2021)
ABSTRACT Objective: This study aimed to evaluate the dimensional stability and maintenance of details of conventional and high stability alginates up to 5-day storage. Methods: Two types of alginates were selected (n=10) for this study, conventional (Hydrogum) and high stability alginates (Hydrogum 5), which were produced with the aid of a cylindrical metal block and a ring-shaped metal mold (Specifications 18, 19, and 25, ANSI/ADA). Ten images were obtained from the molds for the dimensional stability test, which were taken immediately after their production and at each different storage periods (15 min, 24 h, 48 h, 72 h, 96 h, and 120 h) by a digital camera. The specimens were kept hermetically sealed in plastic bags (23°C) and then used to obtain 140 (n=70) dental stone models, used in the detail reproduction test, in which the angular accuracy of three grooves (20 µm, 50 µm, and 75 µm) was observed at each period. The details reproduction accuracy was classified using a predetermined score classification. Measurements of dimensional changes were made in the Corel DRAW X6 program. The data were submitted to the Student's t-test (α?#8197;= 0.05). Results: A statistically significant difference concerning the size of the matrix was observed after 24h for both alginates, and a statistically significant negative linear dimensional change (contraction) was verified after 24 h of storage (1.52% for the high stability alginate, and 1.32% for the conventional alginate). The high stability alginate kept the full details for 72 hours, while the conventional alginate, for 24 h. Both alginates reproduced the 75 µm groove at all storage periods. Conclusion: Impressions made with both alginates presented satisfactory clinical results when the alginates were immediately poured.